Moving beyond fish: working towards integrating human dimensions into sustainable seafood guides from South African perspectives - Ward, Catherine Dale; Pillay, Pavitray; Norton, Marieke (Frontiers in Marine Science, 2024)
Traditionally, seafood assessments and subsequent ratings have guided choice and responsible sourcing of sustainable seafood based primarily on environmental concerns, with limited to no consideration to multi-faceted human dimensions that form an integral part of these complex social-ecological systems. For wild-capture marine fisheries around the world, and particularly in developing countries, human dimensions remain underrepresented in sustainability ratings, where the focus has traditionally been on larger, data-rich commercial fishery components that report predominantly on ecological and management considerations. Yet, addressing the diverse and complex nature of marine social-ecological systems remains critical to achieve global sustainable seafood systems that balance ecological and societal needs to benefit both nature and people. This paper champions the integration of human elements into seafood sustainability guides, building on work reviewing how best to integrate human dimensions into traditional seafood assessments under the World Wide Fund for Nature (WWF) – drawing on examples from South Africa. While the paper does not prescribe a blueprint for implementation, this review highlights challenges and opportunities to include human rights violations and small-scale fisheries in existing sustainable seafood guides from a South African perspective. There is a need for sustainability considerations to move beyond fish to better represent how these social-ecological systems feed into oceanic cultural norms and nutrition. This translates to shifting from an ecological focus to include human dimensions to better represent complex marine social-ecological systems and drive equitable change within local and global seafood industries.